(untitled) (Revista de História Regional, 2007)
The objective of this article is to discuss the teaching of History and the Incorporation of New Technologies of Information and Communication, besides fomenting a reflection of the professionals of the area specially teachers of high school and basic level. This is a pertinent discussion and it is applied to a revision of the teaching of History, aiming at contributing to its improvement and allowing that teachers and students can learn and construct history using new didactic resources.